Seriale, immersivo, industriale. Il barocco e l’invenzione del melodramma - Capaldi, Donatella; Ragone, Giovanni (Mediascapes journal, 2016)
Archetypes of modernity are to be recognized in serial media developed during the first half of XVII century, when a proto-metropolitan social universe was evolving. According to a mediological standpoint, the case study of baroque opera allows to identify the basic characters of consumer genres, and to define connections among serialization, immersivity, virtualization, polisensoriality, hypertextuality, ibridation, chain and work organization, with a special focus on mass audience and on creative reuse of collective imaginary and metaphors. Baroque opera, created for public theatre with admission ticket, was the second pole of an entertainment integrated system consisting of the romance, with its “horizontal” and hypertextual attitude, and of the melodrama, with its immediate and fusional setup: i.e. romance and opera like the ancestors of radio-television fiction and cinema. The birth and rise of the medium “opera” needs to be historicized in the frame of a complex environment study: Venice, as the Italian capital of a cultural proto-industry; the Incogniti Academy as the most important European publishing and entertainment laboratory; and finally, the situation of freedom from censorship, which permitted to libertine network, with its special European relations, to produce new experimental genres often being heterodox on ethical and religious grounds.